A novel protocol of energy–constrained sensor network for emergency monitoring. (25th July 2014) - Wang, Tong; Zhang, Yonghong; Cui, Ying; Zhou, Yucai
The wide employment of wireless sensor networks (WSNs) is hampered by the limited energy constraints of the sensor nodes. Although HEED algorithm leads to a stable distribution of cluster heads, the 'hot zone' and 'isolated cluster' problems remain. For this reason, a routing protocol based on non–uniform hierarchical topologies is proposed (HEEDNH) in this work. By this algorithm, suitable cluster headsets can be obtained, with reduced energy consumption in message broadcasting and balanced cluster nodes and 'isolated clusters' can be eliminated. In the stable stage, an algorithm for emergency monitoring is proposed, which can achieve real–time processing of monitored data and timely feedback to the base station. Finally, a non–uniform layered routing strategy is proposed to solve 'hot zone' problem. Simulation results and theoretical analysis show that the proposed algorithm can increase network lifetime efficiently and make the network better fit emergency monitoring than the traditional protocol.